Speaking Essentials (New York, N.Y. : Films Media Group, 2010)
Does giving a typical business presentation put a person in mortal danger? Of course not, but statistics suggest that many people dread public speaking more than they fear death. This program shows students ways to overcome that kind of paralysis and transform it into positive energy. These include thorough preparation (from learning the wants and needs of the audience to scoping out the location at which the speech will take place) as well as starting with a strong opener, finding the right pace, using nonverbal communication, and more
Basic Overview of Public Speaking (1:18) --Know Your Audience (2:46) --Know Your Space (2:39) -- Be Prepared (4:30) -- A Strong Opener (3:58) -- Using Notes (2:07) -- Nonverbal Communication (1:11) -- Helpful Tips (2:44) -- Closing (1:07) -- How to Wrap Up a Speech (2:13)
Encoded with permission for digital streaming by Films Media Group on July 01, 2010
Films on Demand is distributed by Films Media Group for Films for the Humanities & Sciences, Cambridge Educational, Meridian Education, and Shopware
DVD-R.
Keywords: Oral communication; Oral communication -- Study and teaching; Communication -- Handbooks, manuals, etc; Communication -- Study and teaching; Communication; Interpersonal communication